Antiretroviral therapy does not affect response to chronic hepatitis C therapy in HIV-coinfected patients - Luciana Brosina de Leon; Cristiane Valle Tovo; Dimas Alexandre Kliemann; Angelo Alves de Mattos; Alberi Adolfo Feltrin; Liliane Souto Pacheco; Paulo Roberto Lerias de Almeida (Journal of Infection in Developing Countries)
Introduction: Many patients coinfected with the human immunodeficiency virus (HIV) and hepatitis C virus (HCV) are using highly active antiretroviral therapy (HAART) and HCV therapy with peginterferon (PEG-IFN) and ribavirina (RBV) because the use of direct-acting antivirals is not a reality in some countries. To know the impact of such medications in the sustained virological response (SVR) during HCV treatment is of great importance. Methodology: This was a retrospective cohort study of 215 coinfected HIV/HCV patients. The patients were treated with PEG-IFN and RBV between 2007 and 2013 and analyzed by intention to treat. Treatment-experienced patients to HCV and carriers of hepatitis B were excluded. Demographic data (gender, age), mode of infection, HCV genotype, HCV viral load, hepatic fibrosis, HIV status, and type of PEG were evaluated. One hundred eighty-eight (87.4%) patients were using HAART. Results: SVR was achieved in 55 (29.3%) patients using HAART and in 9 (33.3%) patients not using HAART (p = 0.86). There was no difference in SVR between different HAART medications and regimens using two reverse transcriptase inhibitor nucleosides (NRTIs) or the use of protease inhibitors and non-NRTIs (27.1% versus 31.5%; p = 0.61). The predictive factors for obtaining SVR were low HCV viral load, non-1 genotype, and the use of peginterferon-α2a. Conclusions: The use of HAART does not influence the SVR of HCV under PEG-IFN and RBV therapy in HIV/HCV coinfected patients.